Revisiting the prognostic value of monocyte chemotactic protein 1 and interleukin-6 in the sepsis-3 era - Barre, Max; Behnes, Michael; Hamed, Sonja; Pauly, Dominic; Lepiorz, Dominic; Lang, Siegfried; Akın, Ibrahim; Borggrefe, Martin; Hoffmann, Ursula (Journal of critical care, 2018)
Background: Monocyte Chemotactic Protein 1 (MCP1) and latest sepsis-3 criteria are poorly represented within studies evaluating biomarkers in sepsis. Therefore, this study evaluates the prognostic value of MCP-1 compared to interleukin-6 (IL-6) in patients with sepsis and septic shock according to sepsis-3 criteria. Methods: 136 patients with sepsis or septic shock were included within 24h of intensive care unit (ICU) admission. MCP-1, IL-6, procalcitonin (PCT), C-reactive protein (CRP) and white blood cells (WBC) were measured on days 1, 3 and 8. All-cause mortality was followed up at 30days and 6months. Results: Both MCP-1 and IL-6 levels revealed valuable prognostic discrimination of 30-day and 6-months all-cause mortality on day 1 and 3 (MCP-1: range of AUCs 0.62-0.65, p<0.039; IL-6: range of AUCs 0.65-0.70, p<0.021) compared to PCT, CRP, SOFA and APACHE II score. MCP-1 levels within the 4th quartile revealed the highest mortality at 30days and 6months compared to patients with lower levels (range of hazard ratio (HR)=2.1-3.3, p<0.041). The prognostic value of MCP-1 sustained in multivariate regression models and was comparable to that of IL-6. Conclusion: Both MCP-1 and IL-6 revealed prognostic value for short- and mid-term all-cause mortality in patients with sepsis and septic shock according to latest sepsis-3 definitions.